The centromere and promoter factor 1 of yeast contains a dimerisation domain located carboxy-terminal to the bHLH domain. - Dowell, S J (1992)
CPF1 is a basic helix-loop-helix (bHLH) protein required for optimal centromere function and for maintaining methionine independent growth in yeast. In this work, we show that the region carboxy-terminal to the bHLH domain of CPF1 is essential for CPF1 function in the cell and for dimerisation of CPF1 in solution. The C-terminus of CPF1 contains a potential long amphipathic helix with a hydrophobic face which could provide a suitable protein:protein interface. Point mutations in residues forming this hydrophobic face are sufficient to weaken the interaction between the protein and DNA. By fusing the DNA binding domain or the transcriptional activation domain of GAL4 to the C-terminal 87 amino acids of CPF1, we show that this region is sufficient for mediating protein:protein interactions in vivo. The C-terminal domain of CPF1 can be replaced by the leucine repeat region of the bHLH-ZIP protein USF and the hybrid CPF1-USF protein functions in vivo to provide normal centromere function and methionine independent growth. However, the CPF1-USF hybrid protein is unable to interact with CPF1 suggesting that a dimer of CPF1 is sufficient for maintaining methionine independent growth and normal centromere function.